Sami Fattah And His Role In Arming The Royal Iraqi Air Force 1941-1954 (Journal of the College of Basic Education, 2025)
Sami Fattah made many deals in order to buy planes from Britain and the promise of European countries as well as the United States of America in a separate period of time throughout the period of the position of the Iraqi Air Force Command despite all the difficult circumstances he faced and the events that have become an obstacle in the way of achieving its goals in order to develop power Iraqi air, and the purchase and armament of the aircraft. However, despite all the challenges that prevented the achievement of his curriculum, which he prepared, he was able to achieve his plan, which he drew with his policy and wise leadership.